2009
DOI: 10.1159/000260078
|View full text |Cite
|
Sign up to set email alerts
|

Relevant B Cell Epitopes in Allergic Disease

Abstract: The 3-dimensional structure of an allergen defines the accessible parts on the surface of the molecule or epitopes that interact with antibodies. Mapping the antigenic determinants for IgE antibody binding has been pursued through strategies based on the use of overlapping synthetic peptides, recombinant allergenic fragments or unfolded allergens. These approaches led to the identification of mostly linear epitopes and are useful for food allergens that undergo digestion or food processing. For inhaled allerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 112 publications
3
106
0
1
Order By: Relevance
“…Antibody recognition of many inhalant allergens with globular structures was reported to be conformation-dependent (25). However, several respiratory fungal allergens, such as Asp f 2, Alt a 1, Asp f 1, Asp f 13, Pen n 18, Pen c 13, and Cur l 3, were identified as having linear IgE epitopes (26 -32).…”
Section: Discussionmentioning
confidence: 99%
“…Antibody recognition of many inhalant allergens with globular structures was reported to be conformation-dependent (25). However, several respiratory fungal allergens, such as Asp f 2, Alt a 1, Asp f 1, Asp f 13, Pen n 18, Pen c 13, and Cur l 3, were identified as having linear IgE epitopes (26 -32).…”
Section: Discussionmentioning
confidence: 99%
“…B-and T-cell responses have a defining and differential recognition of antigenic epitopes, and their localization in the allergen does not necessarily coincide. T-cell receptor recognizes only the linear amino acid sequence [59]. In contrast, B-cell epitopes are either linear or conformational and are located on the surface of the molecule accessible to antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Inferences drawn from allergen-antibody complexes and other important studies have shown that majority of IgE-binding epitopes are conformational in nature [14]. IgE epitopes possess some defining structural and immunological features such as they are more cross-reactive in nature and have higher intrinsic flexibility.…”
Section: Ige-binding Epitopesmentioning
confidence: 99%